1998
DOI: 10.1080/00288233.1998.9513336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cattle grazing strategies and pasture species on internal parasites of sheep

Abstract: The results of a three-year study in New Zealand undertaken to compare the effect of alternating sheep and cattle grazing and of different pasture species on internal parasitism in lambs is reported. Despite the commonly held belief that the use of cattle in sheep production systems improves sheep health by reducing nematode burdens, this did not occur. Cattle substantially reduced pasture larval numbers. However, this failed to reduce parasite burdens in lambs as those managed in the absence of cattle apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…Boom & Sheath (2008) found one herbage harvest removed 72% of L 3 , and two harvests reduced L 3 presence to less than 3% of the original population. Moss et al (1998) also found that alternating sheep and cattle grazing reduced sheep pasture L 3 by 82%, with no consistent difference in using 1, 2, 3 or 4 cattle grazings, indicating a large proportion were eliminated after one grazing. We found a similar L 3 reduction for our autumn pats.…”
Section: Herbage Removalmentioning
confidence: 91%
See 1 more Smart Citation
“…Boom & Sheath (2008) found one herbage harvest removed 72% of L 3 , and two harvests reduced L 3 presence to less than 3% of the original population. Moss et al (1998) also found that alternating sheep and cattle grazing reduced sheep pasture L 3 by 82%, with no consistent difference in using 1, 2, 3 or 4 cattle grazings, indicating a large proportion were eliminated after one grazing. We found a similar L 3 reduction for our autumn pats.…”
Section: Herbage Removalmentioning
confidence: 91%
“…al. 1996;Moss et al 1998). These management practices have had varying success and have often been confounded by pasture quality and supply differences.…”
Section: Introductionmentioning
confidence: 99%
“…Na Nova Zelândia, Moss et al (1998) observaram redução na contaminação de piquetes pastajados alternadamente por ovinos e bovinos. Curiosamente, a carga parasitária dos cordeiros que pastejaram os piquetes descontaminados foi similar à dos cordeiros que não compartilharam pastagens com bovinos.…”
Section: Sistema Rotacionado De Pastagensunclassified
“…The Improved system required more conserved feed than did the Control resulting in the Improved system having an annual feed deficit, emulating the experience of Moss et al (1998), when comparing "improved" swards with perennial ryegrass in irrigated systems. Averaged over the 3 years, there was no feed deficit on Proceedings of the New Zealand Grassland Association 62: 59-66 (2000) as the study progressed, and was particularly marked in the Improved grass-based swards.…”
Section: Pasture Performancementioning
confidence: 67%